Biocompatible ceramic-biopolymer coatings obtained by electrophoretic deposition on electron beam structured titanium alloy surfaces - Ramskogler, C.; Cordero, Luis; Warchomicka, F.; Boccaccini, Aldo R.; Sommitsch, C. (Materials Science Forum, 2017)
An area of major interest in biomedical engineering is currently the development of improved materials for medical implants. Research efforts are being focused on the investigation of surface modification methods for metallic prostheses due to the fundamental bioinert character of these materials and the possible ion release from their surfaces, which could potentially induce the interfacial loosening of devices after implantation. Electron beam (EB) structuring is a novel technique to control the surface topography in metals. Electrophoretic deposition (EPD) offers the feasibility to deposit at room temperature a variety of materials on conductive substrates from colloidal suspensions under electric fields. In this work single layers of chitosan composite coatings containing titania nanoparticles (n-TiO2) were deposit by EPD on electron beam (EB) structured Ti6Al4V titanium alloy. Surface structures were designed following different criteria in order to develop specific topography on the Ti6Al4V substrate. n-TiO2 particles were used as a model particle in order to demonstrate the versatility of the proposed technique for achieving homogenous chitosan based coatings on structured surfaces. A linear relation between EPD time and deposition yield on different patterned Ti6Al4V surfaces was determined under constant voltage conditions, obtaining homogeneous EPD coatings which replicate the 3D structure (pattern) of the substrate surface. The present results show that a combination of both techniques can be considered a promising surface modification approach for metallic implants, which should lead to improved interaction between the implant surface and the biological environment for orthopaedic applications.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Electron beam structuring; Electrophoretic deposition; N-TiO2/chitosan; Ti6Al4V